THE ROLE OF VITAMIN D SUPPLEMENTATION FOR HEAD AND NECK CANCER : A LITERATURE REVIEW - Dewi Kania Intan Permatasari; Irna Sufiawati (ODONTO : Dental Journal, 2019)
Background: Vitamin D has several roles, namely physiological function of calcium and bone metabolism, cell growth and differentiation, immune and cardiovascular function. Vitamin D deficiency can cause the risk of cancer. Head and neck cancer is one of the cancers that occur due to vitamin D deficiency in the body. This literature review was to asses and evaluate the impact and benefits of vitamin D supplementation for head and neck cancer.Discussion: A study found an association between vitamin D supplementation and a low risk of recurrence in conditions of high total vitamin D levels. Another study found a significant increase in quality of life (QOL). The primary mechanism of vitamin D action is mediated through binding of either 1,25(OH)2D3 (active form) or 25(OH)D (less active form) to the VDR, which is a member of the nuclear receptor superfamily of steroid and thyroid hormones with gene-regulatory and consequent anti-proliferative properties.Conclusions: Vitamin D supplementation provides a role in improving the condition of patients with head and neck cancer. Both in terms of suppressing recurrence and in terms of increasing quality of life